Management Accounting as an Instrument of Financial Fraud Mitigation - Zulkarnaen, Wandy; Bagianto, Agus; Sabar; Heriansyah, Dasep (International Journal of Psychosocial Rehabilitation, 2020)
Financial fraud in the financial sector of the State of Indonesia reached 43.1 percent, ranking second in Southeast Asia after the State of Vietnam, which amounted to 58.2 percent. The financial fraud is intentional, organized, requires planning, involves false representation, and deceit, and continues to occur despite anti-fraud legislation. This qualitative study explores the perception of a purposive sample of 20 accountants, examiners, and investigators in Indonesia on how to reduce corporate financial fraud. The findings reveal that management accounting is able to reduce fraud; corporate finance requires improvement in education, training, detection, prevention, and internal control. The new fraud mitigation types are emerging that integrate differential agency theory, association theory, and exogenous and endogenous fraud factors that might help explain and predict behavioral patterns exhibited by financial fraud perpetrators.